ANALISIS KETAHANAN PANGAN RUMAH TANGGA PETANI LAHAN KERING DI KABUPATEN SUMBAWA: SUATU TINJAUAN PROPORSI PENGELUARAN PANGAN - Septiadi, Dudi; Yusuf, Muhammad (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2023)
Food security is an important issue in agricultural development in developing countries where the majority of the population depends on the agricultural sector. Poor households have low purchasing power, resulting in access to low quality food and unbalanced food consumption patterns. The aim of this research is to analyze the level of food security of dry land farming households in Sumbawa Regency. The research was conducted in Alas Barat District, Sumbawa Regency, from April to July 2023. The respondents used were 55 farming households who were determined based on the Slovin formula. The data collection technique was carried out using an accidental sampling survey method. Data were analyzed using income analysis and food security analysis based on the ratio approach of the share of food expenditure to total expenditure of farmer households. Analysis of food security is also seen from the aspects of household distribution and income groups. The results of the research show that farmers in the research location are declared as food secure farming households. Based on the distribution, there were 15 farmers who were declared as food insecure households (27.27%). Meanwhile, 40 households (72.73%) were declared food secure farmers. Based on income group, of the 12 high-income farmers, 41.67 percent of them were in the food insecure category.